Multibarrier-penetrating drug delivery systems for deep tumor therapy based on synergistic penetration strategy - Zhang, Hui-Feng; Yu, Huan; Pan, Shuang-Xue; Zhang, Chuang; Ma, Ying-Hui; Zhang, Yan-Fei; Zuo, Li-Li; Hao, Cheng-Yi; Lin, Xiao-Ying; Geng, Hao; Wu, Di; Mu, Shang-Qiang; et al. (Biomaterials science, 2024)
Nanotherapies, valued for their high efficacy and low toxicity, frequently serve as antitumor treatments, but do not readily penetrate deep into tumor tissues and cells. Here we developed an improved tumor-penetrating peptide (TPP)-based drug delivery system. Briefly, the established TPP iNGR was modified to generate a linear NGR peptide capable of transporting nanotherapeutic drugs into tumors through a CendR pathway-dependent, neuropilin-1 receptor-mediated process. Although TPPs have been reported to reach intended tumor targets, they often fail to penetrate cell membranes to deliver tumoricidal drugs to intracellular targets. We addressed this issue by harnessing cell penetrating peptide technology to develop a liposome-based multibarrier-penetrating delivery system (mbPDS) with improved synergistic drug penetration into deep tumor tissues and cells. The system incorporated doxorubicin-loaded liposomes coated with nona-arginine (R 9 ) CPP and cyclic iNGR (CRNGRGPDC) molecules, yielding Lip-mbPDS. Lip-mbPDS tumor-targeting, tumor cell/tissue-penetrating and antitumor capabilities were assessed using CD13-positive human fibrosarcoma-derived cell (HT1080)-based in vitro and in vivo tumor models. Lip-mbPDS evaluation included three-dimensional layer-by-layer confocal laser scanning microscopy, cell internalization/toxicity assays, three-dimensional tumor spheroid-based penetration assays and antitumor efficacy assays conducted in an animal model. Lip-mbPDS provided enhanced synergistic drug penetration of multiple biointerfaces for potentially deep tumor therapeutic outcomes. We co-modified R 9 and iNGR on the liposome surface to obtain Lip-mbPDS. The penetration of Lip-mbPDS into multiple biointerfaces has enabled it to demonstrate good anti-tumor ability for CD13-positive HT1080 cells both in vivo and ex vivo .